ASC speck serum concentrations, a component of sterile cellular inflammation, are associated with individual cardiopulmonary capacity - Kogel, Alexander; Voßhage, Nell; Behzadi, Amirhossein; Laufs, Ulrich; Fikenzer, Sven (Frontiers in Physiology, 2024)
Aims: Exercise-induced cellular stress and sterile inflammation are of increasing interest. ASC specks are a component of the intracellular NLRP3-inflammasome and can be released into the blood. For example, serum ASC specks are increased after marathon running. We therefore tested whether ASC specks are potentially associated with the individual response to physical training and cardiopulmonary capacity.We performed a prospective study in 45 healthy athletes. Blood samples were taken before and after cardiopulmonary exercise testing (CPET). ASC speck concentrations were quantitated using flow cytometry.Results: Baseline ASC speck levels correlated with clinical parameters of body composition (height, weight, BMI) and parameters of cardiopulmonary performance (peak VO2, peak oxygen pulse, heart rate after exercise). Athletes with lowest baseline ASC speck concentrations have a significantly lower BMI (22.0±1.8 vs. 24.9±1.6 kg/m²), higher heart rate at rest (72±10 vs. 58±10 beats/min), lower peak VO2 (2692±629 vs. 3404±747 ml/min) and lower peak oxygen pulse (15.6±3.4 vs. 20.7±3.5 ml/heart rate).Overall, ASC speck concentrations showed no significant change after CPET (7.0±4.5 vs. 8.0±5.4 ASC specks/µl, p=0.3). However, subgroup analysis revealed a significant increase in circulating ASC specks in athletes with the lowest baseline values (2.37±0.84 vs 8.43±7.52 ASC specks/µl, p<0.05). Athletes with an increase in ASC speck concentrations in response to CPET had a lower peak oxygen pulse compared to those with a decrease (17.1±4.2 vs. 19.8±4.1, p<0.05).Low ASC speck baseline values as well as an increase in response to exercise are associated with lower peak oxygen pulse in healthy athletes.